2012
DOI: 10.1007/s10552-012-9957-2
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer survivors at increased risk of subsequent tobacco-related malignancies, United States 1992–2008

Abstract: Purpose-Persistent smoking among cancer survivors may increase their risk of subsequent malignancies, including tobacco-related malignancies. Despite these risks, nearly 40 % of women diagnosed with cervical cancer continue to smoke after diagnosis. This study describes the relative risk of developing any subsequent and tobacco-related malignancy among cervical cancer survivors.Methods-We examined data from the year 1992 to 2008 in 13 Surveillance, Epidemiology and End Results registries. We calculated the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 24 publications
7
30
0
Order By: Relevance
“…A synergistic effect exists between HPV and tobacco . Tobacco is thought to contribute to the progression and malignant transformation of persistent HPV infections of the cervix .…”
Section: Discussionmentioning
confidence: 99%
“…A synergistic effect exists between HPV and tobacco . Tobacco is thought to contribute to the progression and malignant transformation of persistent HPV infections of the cervix .…”
Section: Discussionmentioning
confidence: 99%
“…54 Cervical cancer survivors had a greater risk of additional malignancies associated with tobacco use. 55 Additional research suggested that CRC survivors have higher percentages of obesity and lower levels of physical activity. 56 These studies provide guidance about specific areas that may be targeted to improve survivor education about and self-efficacy related to optimizing health.…”
Section: Cdc Research Portfolio On Health Disparities In Cancer Survimentioning
confidence: 99%
“…The present study demonstrated that only 13% of young women were familiar with the impact of smoking. Underwood et al assessed cervical cancer incidence rate in the USA during the period 1992-2008 and observed that female smokers with cervical cancer were twice more prone to coexistent smoking-dependent cancers [4].…”
Section: Risk Factorsmentioning
confidence: 99%
“…As far as we know today, the main cause of cervical cancer is human papilloma virus (HPV) infection, in particular with high grade oncogenic HPV genotypes, such as HPV-16 and HPV-18, as well as co-occurrence of other factors predisposing women to cancer [1][2][3][4]. According to the WHO, the factors include smoking, multiple sexual partners, low socioeconomic status, herpes simplex virus (HSV) co-infection, human immunodeficiency virus (HIV) infection, and antioxidant and vitamin insufficiency in the diet.…”
Section: Introductionmentioning
confidence: 99%